2017
DOI: 10.18632/oncotarget.14732
|View full text |Cite
|
Sign up to set email alerts
|

Positive expression of Y-box binding protein 1 and prognosis in non-small cell lung cancer: a meta-analysis

Abstract: BackgroundY-box binding protein 1 (YB-1) belongs to the cold shock domain protein family involved in transcription and translation. We conducted a meta-analysis of the association between YB-1 expression and the survival and clinicopathological features in NSCLC.MethodsPubMed and Embase were searched to identify studies that evaluated the YB-1 expression (by immunohistochemistry) and overall survival (OS) in NSCLC. Hazard ratios (HRs) and 95% confidence intervals (CI) of OS were pooled. Odds ratios (ORs) of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
1
7
0
1
Order By: Relevance
“…Analysis of TCGA data shows that elevated YBX1 expression was highly prognostic in a cohort of 1,926 NSCLC patients (Győrffy et al, 2013; Figure 1D) and in 83 mesothelioma patients (Goswami and Nakshatri, 2014; Figure 1E). This supports the results of a recent meta-analysis of data from 692 NSCLC patients which found that high YB-1 protein expression significantly correlated with poorer overall survival and clinicopathological features (Jiang et al, 2017). YB-1 is overexpressed in mesothelioma compared to non-malignant mesothelial cells in vitro (Johnson et al, 2018) and a small study of 33 MPM patients showed a trend toward higher YB-1 expression in sarcomatoid MPM tumors, which are associated with shorter survival (Iwanami et al, 2014).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Analysis of TCGA data shows that elevated YBX1 expression was highly prognostic in a cohort of 1,926 NSCLC patients (Győrffy et al, 2013; Figure 1D) and in 83 mesothelioma patients (Goswami and Nakshatri, 2014; Figure 1E). This supports the results of a recent meta-analysis of data from 692 NSCLC patients which found that high YB-1 protein expression significantly correlated with poorer overall survival and clinicopathological features (Jiang et al, 2017). YB-1 is overexpressed in mesothelioma compared to non-malignant mesothelial cells in vitro (Johnson et al, 2018) and a small study of 33 MPM patients showed a trend toward higher YB-1 expression in sarcomatoid MPM tumors, which are associated with shorter survival (Iwanami et al, 2014).…”
Section: Introductionsupporting
confidence: 89%
“…Analysis of TCGA data demonstrate that high levels of YBX1 mRNA correlate significantly with poor prognosis in NSCLC and MPM patients (Figures 1D,E). YB-1 protein has been correlated with poor prognosis previously (Shibahara et al, 2001; Gessner et al, 2004), supported by a recent meta-analysis of six studies covering data on 692 NSCLC patients, where YB-1 was associated with worse overall survival, tumor stage and depth of invasion (Jiang et al, 2017). A study in MPM patients also supports the TCGA data (albeit tentatively due to the low number of patients in the cohort) (Iwanami et al, 2014).…”
Section: Yb-1 In Thoracic Cancers: Clinical Relevancementioning
confidence: 75%
“…YB-1 is one of the rare proteins that regulates the cellular signaling pathways underlying nearly every cancer hallmark [ 2 , 3 ]. As both a cytoplasmic and nuclear protein, YB-1 is highly expressed in different cancer types, such as breast, lung, colorectal, melanocytic, prostate, ovary, and bone cancer [ 2 , 4 , 5 , 6 , 7 ]. In breast carcinomas, expression of cytoplasmic YB-1 has been shown to be associated with tumor aggressiveness, and nuclear localization was shown to be a predictive marker of recurrence after chemo- and radiotherapy [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Высокая экспрессия этого гена ассо-циирована с ухудшением показателя безрецидивной выживаемости больных РМЖ [12], а также больных с другими новообразованиями [13,14]. Кроме того, белок YB-1 является потенциальной мишенью для тар-гетной терапии [15].…”
Section: обзорные статьиunclassified